A framework for design lean supply chain: a case study in a Peruvian concrete company - Arauco, Ivan (2022)
This paper seeks to demonstrate the positive effects of a lean supply chain at a concrete company. Management of this lean SC illustrates a new lean SC approach in the Peruvian construction industry. This case study provides a lean SC framework. The proposed methodology is introduced step-by-step according to lean management concepts; each step uses lean tools: visual management, 5S methodology, and standardised work. The findings demonstrate the viability of the methodology. We summarise the results and conclusions obtained in the research. These specific tools improved metrics in each SC process studied: source, make, and deliver. Delivery times were improved by 20%, and SC costs were reduced by 8%. This case study shows the benefits of costs and time. It demonstrates that the lean SC framework and tools applied to an integrated SC achieved exceptional operational results.